As contaminações da carne bovina e a associação com as características do sistema de inspeção sanitária do RS: uma análise de regressão de contagem multinível - Rodrigues, Daniel (Universidade do Vale do Rio dos Sinos, 2013)
Nowadays, the cases of interruption at the beef supplying chain in Brazil, are connected, mainly, to the events of contamination. Although the majority of contamination sources are linked to the country area (subsystem production), it is inside the industries (subsystem industrialization) that are inserted the conditions, more appropriated, theoretically, to the effective control in these events. For that reason, related to the importance at the supplying chain, the subsystem industrialization can be considered the linking that causes more impact to the sanity and quality of the final product. This research aimed to analyze how the characteristics of the Sanitary Inspection System are linked to the detection of contamination cases at the beef supply chain. The sample is composed by 103 cold-store buildings, certificated with the state inspection stamp, and by 19 Regional Units of Inspection in Rio Grande do Sul. To statistical analyzes, the used technique was the regression analysis at multilevel counting, being one of the most relevant facts to the choice the preservation of hierarchic levels of data. Related to the Sanitary Inspection System, the results point to the influence of aspects as the number of Considered Companies, Inner Resources and the Coefficient of Variation of Slaughtering at the cases of detected contamination. Related to the Company, the results point to the transport, defined from the number of animals slaughtered, presented relation to the cases of contamination detected. In the tests of interaction between the variables of different levels, Animals Slaughtered (Company level) showed an interaction considered meaningful with a variable of second level of the Inner Resources (Resources level). To the light of Institutional Theory, it was confirmed the rule of the State as an important force of coercion of the environment (regulative isomorphism) that pressures the companies so that they become more homogeneous, mainly, in the operations of slaughtering and it ratifies that the professions (normative isomorphism), through the Veterinarian and Assistant of Inspection, also consists in an important force of the environment that induces the packing plants to be similar. In the management implications, the results indicate that the System of Sanitary Inspection has a considerable association with the Detected events of Contamination, mainly, for factors as the internal structure of the 8 Regional Unit, the capacity and amount of supported requests, and the structural conditions of attended companies.
Keywords: Cadeia de suprimentos da carne bovina; Contaminações; Teoria institucional; Sistema de inspeção sanitária; Análise de regressão multinível; Beef supply chain; Contamination; Institutional theory; Sanitary inspection system; Analysis of multilevel regression; ACCNPQ::Ciências Sociais Aplicadas::Administração